The Problem of Establishing Regions in Iraq And the extent of their impact on the relationship of the Kurdistan Region to the federal authority - امىدرس امدكخِر ملىان عىر حصٔي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
This research entitled (The Problematic Establishment of the Regions in Iraq and the extent of their Effect on the relationship of the Kurdistan Region to the federal authority) analytical study, contain an introduction and three paragraphs followed by a conclusion. This study aims to clarification the problem of the formation of the federal state in Iraq and the extent of the effect of one region within Iraqi Federal Framework and the opposition to establishing new Regions in Iraq despite of the existence of the constitutional and legal foundations for the establishment of regions in Iraq, on the future relationship between the Kurdistan Region and the federal authority, And therefore the survival and continuance of the federal system in Iraq. In general, this study includes various aspects related to the subject of the research in legal, political and constitutional stand point, and I reached some facts, conclusions and proposals, one of the most important of conclusions which is that the Iraqi government and other Iraqi components, Especially the Shiaa component has retreated from the federal system which is approved by the Iraqi Constitution of the year 2005 and that strongly opposed the establishment of new Regions in Iraq so as not to achieve the Federal Union in Iraq and return to the simple state, so we find that the thinking became more serious in the Kurdistan Region towards independence by holding a general referendum on 25/9/2017